Inflammatory root resorption in primary molars: prevalence and associated factors - Vieira-Andrade,Raquel Gonçalves (2012)
This study aimed at determining the prevalence of inflammatory root resorption and associated factors in 1068 primary mandibular molars in 453 children 3 to 12 years of age. Age, dental history and medical history were recorded using a questionnaire administered to the children's parents/caregivers. Previously trained and calibrated examiners assessed radiographic images of the primary molars by direct observation, with the aid of a viewing box. Root resorption (physiological or inflammatory), dental crown status (healthy, carious with no pulp involvement, carious with pulp involvement and evidence of restoration), and pulpotomy or pulpectomy were determined. Data analysis involved descriptive statistics, the chi-square test and a multiple logistic regression (p < 0.05). The prevalence of inflammatory root resorption was 16.2% (n = 173). The male gender (OR: 1.4; 95% CI), the 3-to-7-years age bracket (OR: 1.5; 95% CI), an unhealthy dental crown (OR: 8.7; 95% CI), caries with pulp involvement (OR: 7.4; 95% CI), pulpotomy (OR: 3.1; 95% CI), and pulpectomy (OR: 5.4; 95% CI) were risk factors for the occurrence of inflammatory root resorption in primary molars. In conclusion, the prevalence of inflammatory root resorption in the present sample was 16.2%. Gender, age, an unhealthy tooth, caries with pulp involvement, pulpotomy, pulpectomy, and the absence of a restoration were associated with a higher occurrence of inflammatory root resorption in primary molars.